Registered trader participation during the Toronto Stock Exchange's pre-opening session - Ryan Davies (Queen's University, Department of Economics, 2000)
This paper documents order submission strategies during the Toronto Stock Exchange's pre-opening session. I find that the registered trader (RT) actively participates in the market opening despite not being able to set the opening price directly and not having an apparent informational advantage. I find that RT opening trades are profitable, are able to moderate overnight price changes, and may be motivated, in part, by inventory adjustment concerns. I focus on interlisted stocks that simultaneously open for trading under two different mechanisms and show how the comparative levels of pre-trade market transparency of each exchange impacts RT profits and participation.
Keywords: g10; 330; Registered trader; market transparency; interlisted securities; price discovery